Infectious Diseases as Socio-Spatial Processes: The COVID-19 Outbreak In Germany - Andreas Kuebart; Martin Stabler (Tijdschrift voor economische en sociale geografie, 2020)
This paper argues that outbreaks of infectious diseases should be understood as socio-spatial processes with complex geographies. Considering the different dimensions of space through which an outbreak unfolds, facilitates analysing spatial diffusion of infectious disease in contemporary societies. We attempt to highlight four relevant dimensions of space by applying the TPSN framework to the case of the recent COVID-19 outbreak in Germany. By identifying key processes of disease diffusion in space, we can explain the spatial patterns of the COVID-19 outbreak in Germany, which did not feature the well-known patterns of spatially contagious as in or hierarchical diffusion. In contrast, we find superspreading events and especially relocation diffusion based on existing networks, on which the pathogen travelled like a blind passenger, to be more relevant. For us, these findings prove the value of combining relational thinking with geographic analysis for understanding epidemic outbreaks in contemporary societies. This paper argues that outbreaks of infectious diseases should be understood as socio-spatial processes with complex geographies. By analyzing the early weeks of the COVID-19 outbreak in Germany in 2020, we highlight the relevance of superspreading events and especially relocation diffusion based on existing networks, on which the pathogen travelled like a blind passenger.
Keywords: 330; Infectious Disease; COVID-19; Health Geography; TPSN; Disease Diffusion; Germany